INTRODUCING A VEGETARIAN DIET TO THE DAILY FIELD SET OF PRODUCTS FOR MILITARY SERVANTS BASED ON THE EXPERIENCE ARMIES MEMBER COUNTRIES OF NATO - Pavlenko, Serhii; Kuprienko, Yuliia; Mogylevska, Viktoriia (Honor and Law, 2023)
The introduction NATO standards into the components security and defense sector is one of the priority tasks for our country on the way to the Alliance. This topic remains relevant for more than one year. One of these standards is taking into account the specifics of military servicemenʼs diet, including vegetarian servicemen. There are a significant number of servicemen in National Guard of Ukraine units and other military formations who do not consume meat and animal products. The main reasons for this are: ethical views; theism and observance of certain fasts; various disorders of the body (restricted ability of the body to absorb lactose, periodic problems with digestion), etc. With the start of a full-scale war in 2022, Ukrainian volunteers covered the most diverse needs of the army. It was not an exception to meet the needs of some servicemen in National Guard of Ukraine and other military formations in vegetarian dry rations. Being a military serviceman, a person has certain limitations in the choice of food, since in many situations it depends on what exactly the state provides him with (the difficulty or complete lack of opportunities to buy food and prepare it independently plays a role). The introduction of additional ones to the existing dry rations, which can take into account these features, can solve this problem, in particular, in the absence of a "kitchen", namely in the areas of direct performance of tasks. The lack of plant-based meals causes many military personnel to abandon their ethical principles and, as a result, suffer health problems due to a forced and drastic change in diet after years of veganism. Thus, taking into account the experience of the worldʼs leading armies can fundamentally improve the organization of food supply in terms taking into account certain needs of military personnel. Also, it should be understood that the introduction of vegetable dry rations is not a change in the nutrition itself in the National Guard of Ukraine, but only its addition and expansion.